2021
DOI: 10.1111/bpa.12936
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and dementia‐related synaptopathy in the hippocampus after military blast exposures

Abstract: Explosive shockwaves, and other types of blast exposures, are linked to injuries commonly associated with military service and to an increased risk for the onset of dementia. Neurological complications following a blast injury, including depression, anxiety, and memory problems, often persist even when brain damage is undetectable. Here, hippocampal explants were exposed to the explosive 1,3,5-trinitro-1,3,5-triazinane (RDX) to identify indicators of blast-induced changes within important neuronal circuitries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Recently, several studies have shown that SIRT1 plays a significant role in induced neuroprotection following caloric restriction (CR) 27 , 28 . CR has also been linked to reduced tau phosphorylation and maintenance of hippocampal neurons 29 , and related Tau pathology is known to be implicated in different types of TBI 30 , 31 . While CR has been shown to increase ketone bodies in the blood, KD does this at a higher level 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that SIRT1 plays a significant role in induced neuroprotection following caloric restriction (CR) 27 , 28 . CR has also been linked to reduced tau phosphorylation and maintenance of hippocampal neurons 29 , and related Tau pathology is known to be implicated in different types of TBI 30 , 31 . While CR has been shown to increase ketone bodies in the blood, KD does this at a higher level 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The explants displayed long‐term maintenance of the major neuronal subfields of the hippocampus (Figure 1B) and their dense processes populated with evident staining of synaptic terminals (Figure 1C–E). Former studies reported that the slice cultures exhibit connectivity, plasticity and pathogenic responsiveness as found in vivo 11,13,50–52 . Here, we used an NMDA infusion period that led to pathogenic changes as previously described 6,51 …”
Section: Resultsmentioning
confidence: 99%
“…Former studies reported that the slice cultures exhibit connectivity, plasticity and pathogenic responsiveness as found in vivo. 11 , 13 , 50 , 51 , 52 Here, we used an NMDA infusion period that led to pathogenic changes as previously described. 6 , 51 The protocol for the excitotoxic stimulation and subsequent measuring of gene expression profiles is shown in Figure 1F , in which the explants were infused with NMDA for 20 min followed by rapid washout in the presence of glutamatergic antagonists for precise insult duration due to quenching any further excitatory activation.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the completion of studies using POD device in rats, we will work with Impel Neuropharma (human POD device) to optimize IN delivery to humans. In addition to benefitting cortical impact injuries, NSCs could also impart benefits in others CNS injury models such as ischemic or hemorrhage stroke [32][33][34][35] and blast-induced injuries 81,82 . Thus, development of cellular therapy of therapeutic NSCs delivered IN represents a promising method for treating patients with a wide range of TBI and other CNS pathologies [83][84][85] .…”
Section: Discussionmentioning
confidence: 99%